2021
DOI: 10.1212/wnl.0000000000011932
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Racial and Ethnic Differences in Cerebral Small Vessel Disease Subtype and Burden to Risk of Cerebral Hemorrhage Recurrence

Abstract: ObjectiveBlack and Hispanic survivors of intracerebral hemorrhage (ICH) are at higher risk of recurrent intracranial bleeding. MRI-based markers of chronic cerebral small vessel disease (CSVD) are consistently associated with recurrent ICH. We therefore sought to investigate whether racial/ethnic differences in MRI-defined CSVD subtype and severity contribute to disparities in ICH recurrence risk.MethodsWe analyzed data from the Massachusetts General Hospital ICH study (n = 593) and the Ethnic/Racial Variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“… 30 Furthermore, epidemiologic studies have demonstrated racial and ethnic differences in cSVD manifestations and burden, which may have a genetic component. 32 These findings underline the importance of extending future genetic studies to include a broader range of ethnic groups.…”
Section: Discussionmentioning
confidence: 96%
“… 30 Furthermore, epidemiologic studies have demonstrated racial and ethnic differences in cSVD manifestations and burden, which may have a genetic component. 32 These findings underline the importance of extending future genetic studies to include a broader range of ethnic groups.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a manual search was performed and 11 articles were added to the meta‐analysis. Of the 41 finally included studies, most reported the association of CSVD with functional outcome (20/41) [13–15,20–24,27–31,34,36,38–42] and stroke recurrence (17/41) [10,17,18,33,37,40–42,50–58] and only a few involved mortality (5/41) [11,16,22,35,38] and HE (7/41) [12,19,25,29,31,32,39]. It is worth mentioning that nine included studies on CMB and stroke recurrence did not provide information on the relationship between them [50–58], but the authors of a meta‐analysis sought data from their authors to explore this relationship [59].…”
Section: Resultsmentioning
confidence: 99%
“…WMH was associated with short-term poor functional outcome and mortality after ICH in a recent meta-analysis of nine studies [26]. An increasing number of studies have subsequently provided comprehensive evidence [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. It is plausible that different subtypes of CSVD markers have different effects on the clinical prognosis of patients with ICH.…”
Section: Introductionmentioning
confidence: 99%
“…However, for brevity, we will simply refer to it as CSVD. The aging of the population is closely related to the occurrence of CSVD, but the contribution of ethnicity in CSVD needs to be further confirmed by epidemiological studies ( 7 , 8 ). CSVD increases the risk of acute stroke more than 2-fold ( 9 ), and its classical form is characterized by cognitive impairment or dementia, motor dysfunction, and psychobehavioral abnormalities.…”
Section: Introductionmentioning
confidence: 99%